Age, Body Weight, Body Mass Index, and Sleep Duration In Predicting Hypertension Incidence At Productive Age in Medan City - Darren Gosal; Yohanes Firmansyah; Ernawati Ernawati (Yayasan Pendidikan Medika Indonesia, 2021)
Hypertension defines as elevated blood pressure with systolic blood pressure above 140mmHg and/or diastolic blood pressure above 90mmHg. Hypertension affects 1,13 billion worldwide, mainly in low and middle-income countries. Generally, the classification of hypertension is divided into optimal, normal, high normal, grade 1, grade 2, and grade 3. Age, body weight, body mass index, and sleep duration can increase the risk of hypertension incidence. This study aimed to determine the cut off value of each variable to predict the hypertension incidence in Medan city. 352 respondents assessed with subjective questionnaire, blood pressure measurement, body weight, height and analyzed with Mann Whitney, ROC curve, and last Chi-Square with Yates correction. All variables were significantly associated (p-value<0,001) with hypertension incidence with cut off values: 45 years old, lower than 5,5 hours per night, greater than 65 kg for the body weight, and greater than 25 kg/m2. Age, body weight, body mass index, and sleep duration were associated and can be a good predictor for hypertension incidence.